Symptomatic vs. Asymptomatic 20–40% Internal Carotid Artery Stenosis: Does the Plaque Size Matter? - Elhfnawy, Ahmed Mohamed; Volkmann, Jens; Schliesser, Mira; Fluri, Felix (Frontiers in Neurology, 2019)
Background: Around 9-15% of ischemic strokes are related to internal carotid artery (ICA)-stenosis ≥50%. However, the extent to which ICA-stenosis <50% causes ischemic cerebrovascular events is uncertain. We examined the relation between plaque cross-sectional area and length and the risk of ischemic stroke or TIA among patients with ICA-stenosis 20-40%. Methods: We retrospectively identified patients admitted to the Department of Neurology, University Hospital of Würzburg, from January 2011 until September 2016 with ischemic stroke or TIA and concomitant ICA-stenosis 20-40%, either symptomatic or asymptomatic. Plaque length and cross-sectional area were assessed on ultrasound scans. Results: We identified 41 patients with ischemic stroke or TIA and ICA-stenosis 20-40%; 14 symptomatic and 27 asymptomatic. The plaque cross-sectional area was significantly larger among symptomatic rather than asymptomatic ICA-stenosis; median (IQR) were 0.45 (0.21-0.69) cm2 and 0.27 (0.21-0.38) cm2, p=0.03, respectively. A plaque cross-sectional area ≥0.36 cm2 had a sensitivity of 71% and a specificity of 74%, in favor of symptomatic rather than asymptomatic ICA-stenosis. In a sex-adjusted multivariate logistic regression, a plaque cross-sectional area ≥0.36 cm2 and a plaque length ≥1.65 cm were associated with an OR (95% CI) of 5.54 (1.2-25.6), p=0.028 and 1.78 (0.36-8.73), p=0.48, respectively, for symptomatic ICA-stenosis. Conclusion: Large plaques might increase the risk of ischemic stroke or TIA among patients with low-grade ICA-stenosis 20-40%. Sufficiently powered prospective longitudinal cohort studies are needed to definitively test the stroke risk stratification value of carotid plaque length and cross-sectional area in the setting of current optimal medical treatment alone.